The effect of music education on students' psychological well-being - Javad Mehraban (Institute of Management fekrenoandish, 2020)
The present study was conducted to investigate the role of music education on students' psychological well-being. The method of this study was causal - comparative, and the statistical population of this study was Tonekabon high school students in the academic year of 2009-2010. The sampling method was targeted, with 100 students in two groups of music and normal students. The measurement tool in this study was Reef's psychological well-being scale (1989). The results of this study showed that the average rank of psychological well-being of students is equal to 71.61 and of non-students is equal to 29.84, and the Z test value is equal to 7.123 at the level of 0.01significance. Thus, music education has had an effect on students' psychological well-being (P <0.01). By including music education programs as an independent curriculum, steps can be taken to promote the students' mental health indicators.